2016
DOI: 10.1108/mrr-11-2015-0271
|View full text |Cite
|
Sign up to set email alerts
|

The role of information alignment and entrepreneurial traits on SME internationalization

Abstract: Purpose – The paper aims to explore the internationalisation decision-making of small- and medium-sized enterprise (SME) owner/managers. Specifically, structural alignment theory (SAT) and regulatory focus theory (RFT) are utilised to examine the concept of opportunity recognition in the context of internationalisation choices. Design/methodology/approach – This paper is conceptual in nature, and an integrative cognitive model of interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 75 publications
(168 reference statements)
0
8
0
1
Order By: Relevance
“…1 Pinho (2007) showed that the entrepreneur's ability to innovate and its international experience are positively associated with an equity-based entry mode. This lack of attention to the individual level does not only contradict general small business and entrepreneurship literature (Shepherd, 2011), but also ignores SME internationalization research (Oviatt and McDougall, 2005) where it is argued that the manager / owner is in the centre of the entrepreneurial decision-making process (Bruneel and De Cock, 2016;Peschken et al, 2016). Given that motivational dispositions and specifically deep-rooted implicit needs energize individuals and predict stable, long-term behaviour (Schultheiss and Brunstein, 2010;Slabbinck et al, 2018) In sum, even though the body of knowledge on the pre-internationalization phase thus shows that individual aspects such as risk perception (e.g., Acedo and Jones, 2007;Shrader et al, 2000), higher education levels (e.g., Amorós et al, 2016) or international experience (Child and Hsieh, 2014) impact the decision to internationalize and its timing, the specificities on the impact of such individual aspects in specific sub-domains are under-researched (e.g., Bruneel and De Cock, 2016) and the number of studies on deeper-level psychological and behavioural aspects is still surprisingly low (Acedo and Florin, 2006;Geh, 2010;Peschken et al, 2016).…”
Section: Current State-of-the-art Of the Micro-foundations Of Small Bmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Pinho (2007) showed that the entrepreneur's ability to innovate and its international experience are positively associated with an equity-based entry mode. This lack of attention to the individual level does not only contradict general small business and entrepreneurship literature (Shepherd, 2011), but also ignores SME internationalization research (Oviatt and McDougall, 2005) where it is argued that the manager / owner is in the centre of the entrepreneurial decision-making process (Bruneel and De Cock, 2016;Peschken et al, 2016). Given that motivational dispositions and specifically deep-rooted implicit needs energize individuals and predict stable, long-term behaviour (Schultheiss and Brunstein, 2010;Slabbinck et al, 2018) In sum, even though the body of knowledge on the pre-internationalization phase thus shows that individual aspects such as risk perception (e.g., Acedo and Jones, 2007;Shrader et al, 2000), higher education levels (e.g., Amorós et al, 2016) or international experience (Child and Hsieh, 2014) impact the decision to internationalize and its timing, the specificities on the impact of such individual aspects in specific sub-domains are under-researched (e.g., Bruneel and De Cock, 2016) and the number of studies on deeper-level psychological and behavioural aspects is still surprisingly low (Acedo and Florin, 2006;Geh, 2010;Peschken et al, 2016).…”
Section: Current State-of-the-art Of the Micro-foundations Of Small Bmentioning
confidence: 99%
“…Amor os et al, 2016) or international experience (Child and Hsieh, 2014) impact the decision to internationalize and its timing, the specificities on the impact of such individual aspects in specific sub-domains are under-researched (e.g. Bruneel and De Cock, 2016) and the number of studies on deeper-level psychological and behavioural aspects is still surprisingly low (Acedo and Florin, 2006;Geh, 2010;Peschken et al, 2016).…”
Section: Sme Internationalization and The Entrepreneurmentioning
confidence: 99%
See 1 more Smart Citation
“…the SI of Vanderstraeten et al, 2020). Especially in small firms, where key decision-makers directly shape the agenda, their motivations and orientation are of central importance (Peschken et al, 2016). Yamakawa et al (2008) considered entrepreneurial orientation (EO) an important firm-specific capability and factor for OFDI decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, SMEs make substantial contributions to national output and growth, exports and employment creation resulting in improved Gross Domestic Product (GDP) for a country. The contribution of SMEs to economies is widely acknowledged by both academics and policymakers (Peschken, 2016). Many developing economies are confronted with challenges such as low output from industry, high graduate unemployment, poor resource utilisation, influx of foreign goods unto the local domestic market leading to increased competition among others.…”
Section: Introductionmentioning
confidence: 99%